PEMBERDAYAAN UMKM MELALUI PENINGKATAN MOTIVASI BERUSAHA DI DESA KRAKAL KECAMATAN ALIAN KABUPATEN KEBUMEN (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Motivation is very important in every activity. Motivation influences enthusiasm, as does effort. The enthusiasm for business in Krakal village has experienced a decline due to Covid-19. This decline can be seen from the sluggish business activities in Krakal village. Most of the business activities in Krakal village are known. A person's weak motivation is influenced by several things such as sluggish economic activity due to the impact of Covid-19, the lack of capital they have and the lack of encouragement or motivation from the surrounding environment. The aim of service activities is to help increase interest and enthusiasm for entrepreneurship and introduce digital marketing. Strategic Plan by increasing the knowledge of citizens to have knowledge and understanding about increasing motivation and understanding of digital marketing. . Strategy Target by increasing knowledge about the importance of motivation in carrying out business activities and the importance of using digital marketing to expand the marketing of products produced